Polska Nowa Zelandia : migracja lat 1945-2006 - Zdziech, Dariusz (2022)
A brief history of Polish emigration to New Zealand until the end of the World War 2 is presented first, setting a background to the main topic of the book. Then in the next chapter, all attention is given to the post-war period. Each wave of newcomers, beginning with groups of ex-soldiers arriving to join with members of their family and ending with a recent group of mostly young professionals aiming at making a successful career on the antipodes, has been analysed with considerable detail. The following chapter looks at the stance the Polish immigrants took towards the Polish communist Government in Warsaw including its diplomatic post in Wellington. This has been thoroughly analysed. It shows the patriotism of the Polish communities. With admirable determination they felt allegiance to and strongly supported the Polish Government in London – in exile until 1990. The final chapter deals with the attitude of Polish immigrants toward the host country and the local government in Wellington. Legal matters regarding residency, citizenship, work and so on, together with motives of coming and settling in this country, becoming a loyal citizen, are all presented in attempt to determine the national consciousness of the immigrants – are they still Polish or more New Zealanders by now? Although there is no one answer to that question, it seems certain that regardless of the opinion one or another individual holds toward their home country, in times of trouble or glory, they do remember their Polish roots. The source of the wide material presented in this book came from extensive queries done in New Zealand, Great Britain, Switzerland, Austria and Poland. Most valuable were numerous interviews with ‘Polish Kiwis’ living in various places in New Zealand. They were conducted while the author was on his New Zealand leg of his research.
Keywords: Polonia; emigration; New Zealand